MAKNA SIMBOLIK DALAM BL SERIES THAILAND BAGI PENGGEMARNYA - ANDRIANI, ASTRI DWI; Siti Fatimah Azzahra; Zikri Fachrul Nurhadi3; Aminah Agustinah (STISIP Widyapuri Mandiri Sukabumi, 2024)
This research by Siti Fatimah Azzahra, Communication Science study program of Putra Indonesia University Cianjur, which the research title is